The impact of Covid-19 to the Cyber Security and information society – experience of Malaysia = Dampak Covid-19 terhadap keamanan cyber dan masyarakat informasi – pengalaman Malaysia - Zulhuda, Sonny (2020)
This keynote presents and analyses the impact of Covid-19 pandemic crisis on cybersecurity. It highlights that the flocking of people to online platforms brings about the increasing rise of threats to cybersecurity. Risks of over-surveillance, data exploitation, and misinformation arose, and one needs to ensure proper governance of his online activities. Legal measures that address these risks, especially from the Malaysian perspective.